Mobile Phone sebagai Reminder Upaya Meningkatkan Kepatuhan Pengobatan ARV pada Orang dengan HIV - Yunita Devianti; Agung Waluyo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to analyze and determine the most effective method of utilizing the Mobile Phone application as a reminder to improve ARV treatment adherence. This study uses a narrative literature review method using keywords from the Scopus, ProQuest, Ebsco, Science Direct, and Pubmed databases. The study's results using this method are effective in utilizing mobile phones to improve ARV treatment adherence in HIV patients. As a reminder, the mobile phone method can improve ARV treatment adherence in HIV patients is a trend in changing lives. Meanwhile, direct intervention is an educational approach that is comprehensive in emphasizing health problems independently in ARV treatment adherence. In conclusion, both produce outputs, namely increasing commitment to ARV treatment in people with HIV, knowledge about HIV, and reducing stigma in people with HIV. Keywords: HIV, Mobile Phone Reminder, ARV Treatment